Effect of Public Debt on The Trade Balance in Iraq For The Period (2003-2021) - Sheeaa Marie, Burhan; Shaker Moslem, Hamdya (Journal of Economics and Administrative Sciences, 2023)
Despite the significant increase in public spending in Iraq, it was not directed toward the important sectors that have an important role in correcting the productive structure. Rather, most of the public expenditure was going to cover the required imports, or to face shocks, whether security or health, and this caused a continuous decrease in the volume of Iraq’s exports of goods and services, as the aim of the study was to review the importance of public debt and its impact on the trade balance, as well as to know the economic policies that can contribute to strengthening the trade balance, as the study proved through the (ARDL) model that there is a direct relationship between the domestic debt and the net trade balance, and an inverse relationship with regard to the external debt and the trade balance, as an increase in the external debt by one unit leads to a decrease in the net trade balance, and the study came out With several recommendations, the most important of which is directing public debt funds, whether domestic or external, to build and expand productive capacity. That borrowing be only for public investment, not consumption. As well as supporting the private sector as the main engine of productive sectors.